Pengembangan Trainer Battery Management System untuk Meningkatan Hasil Belajar Siswa Sekolah Menengah Kejuruan - Afrianto, Dimas; Utomo, Aryo Baskoro (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
The rapid growth of renewable energy technology has increased the demand for skilled workers capable of adapting to modern energy systems. Battery Management Systems (BMS) are used to monitor and protect batteries, ensuring safe and efficient energy storage operations. In vocational education, particularly at Vocational High Schools (SMK), mastering BMS technology is essential for developing competencies aligned with industrial needs in the field of Industrial Electronics Technology and the subject of Electronic Circuit Applications. However, teaching the concept of energy storage remains a challenge. Batteries, as crucial components in solar, hydro, and hybrid power systems, require a deep understanding of their characteristics and management. This study aims to analyze the impact of using a BMS trainer to improve student learning outcomes. The trainer simulates real-world systems with charging, discharging, and balancing functions, supporting contextual and practice-based learning. The development process followed the ADDIE model and was implemented at SMKN Jawa Tengah and SMKN 4 Semarang. Validation results indicated excellent feasibility, with scores of 89% from subject matter experts and 85% from media experts. Learning outcomes were evaluated using pretest–posttest and paired t-tests, showing significant improvement, with N-Gain scores of 80.8% at SMKN Central Java and 77.7% at SMKN 4 Semarang, and cognitive gains of 28.33 and 33.58 points, respectively. These findings confirm that the BMS trainer effectively enhances students’ understanding of renewable energy concepts.